PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS MEDIA GAMBAR LEGENDA TELAGA NGEBEL UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS VI SD NEGERI KEPET 02 - Ari Purwantono; Jeffry Handhika; Dwi Rosita Sari (An Nafi': Multidisciplinary Science, 2026)
This study aims to describe the implementation and improvement of simple essay writing skills through the Problem-Based Learning (PBL) model, based on images of the legend of Lake Ngebel, among sixth-grade students at Kepet 02 Elementary School in Madiun Regency. The main problem in this study was the low quality of students' writing and the lack of use of innovative media in learning. The method used was Classroom Action Research (CAR), consisting of the pre-cycle, Cycle I, and Cycle II stages. The results showed a significant increase in student activity and learning outcomes. In the pre-cycle stage, the average activity and essay quality scores were in the low category (score 2.00). After implementing the PBL model, students' active involvement in discussions and their ability to compose coherent essays increased dramatically. The conclusion of this study is that the integration of local wisdom through images in the PBL model effectively improves students' writing skills and cultural literacy